Tinjauan Etika Bisnis Islam pada Sanksi Blacklist terhadap Konsumen - Nia Wulansari; Titin Suprihatin (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. A businessman must apply the principles of truth by reflecting a spirit of generosity, a good motive for service, and an attitude toward god's begetting. From principles of righteousness a business automatically gives birth to brotherhood. Business is in the online shop Quenney.id carries a penalty for the consumer which is blacklist sanctions. The purpose of this study is to find a review of the Islamic business ethics regarding the application of blacklist sanctions mechanisms for online shop Queneey.id. These research methods are qualitative. The result of this study is the blacklist sanctioned mechanism given not on the basis of the damage but only for the benefit of the online shop. Which has left consumers unable to communicate and communicate again. This is not in accordance with the ethical principles indicator of the Islamic business's loose generosity and the building of good relations and the ethical concept of the Islamic business. This led to the failure of ethics toward consumers And consumer rights are unfulfilled. Abstrak. Seorang pembisnis harus menerapkan prinsip kebenaran dengan mencerminkan sikap kemurahan hati, motif pelayanan yang baik, dan sikap akan adanya Allah SWT. Bisnis dalam Online Shop Queneey.id menerapkan sanksi bagi konsumen yaitu sanksi blacklist. Tujuan dari penelitian ini untuk mengetahui tinjauan Etika Bisnis Islam terhadap mekanisme penerapan sanksi blacklist (daftar hitam) terhadap konsumen pada online shop Queeney.id. Metode penelitian ini adalah kualitatif. Hasil dari penelitian ini adalah mekanisme pemberian sanksi blacklist ini diberikan tidak atas dasar adanya kerugian melainkan hanya untuk kepentingan online shop. Yang mengakibatkan konsumen tidak dapat bertranskasi dan berkomunikasi lagi. Hal ini tidak sesuai dengan indikator prinsip etika bisnis Islam longgar bermurah hati dan membangun hubungan baik serta konsep etika bisnis Islam. Hal ini mengakibatkan etika kepada konsumen tidak terlaksana dan hak konsumen tidak terpenuhi .